Strategi Pengembangan Jangka Panjang Pada Koperasi Konsumen Karyawan Eccindo Indonesia Untuk Meningkatkan Kesejahteraan Anggota - Atika Muhfida Hanum; Aida Fitria; Kafidin Muzakki (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research discusses the long-term development strategy of the Eccindo Indonesia Employee Consumer Cooperative to improve member welfare through qualitative methods by means of interviews and surveys with employees and members of the Eccindo Indonesia Employee Consumer Cooperative. The analysis techniques used by researchers are SWOT and Porter's Five Forces Analysis. The aim of this research is to find out the long-term development strategy of the Eccindo Indonesia employee consumer cooperative to improve the welfare of members. It is hoped that the research findings will contribute to readers' understanding of the development of employee consumer cooperatives, as well as serve as a guide for efforts to improve members' welfare through long-term, sustainable strategies.